2015
DOI: 10.4103/0973-1296.153065
|View full text |Cite
|
Sign up to set email alerts
|

Anti-arthritic activity of Fu-Fang-Lu-Jiao-Shuang on collagen-induced arthritis in Balb/c mice and its underlying mechanisms

Abstract: Background:Rheumatoid arthritis (RA) is a common, autoimmune disorder characterized by progressive multiple joint destruction, deformity, disability and premature death in most patients. Fu-Fang-Lu-Jiao-Shuang (FFLJS) is an effective traditional Chinese medicine, which has long been used clinically to treat RA patients.Objective:The objective of this study is aimed to evaluate the anti-rheumatic effects of FFLJS on collagen induced arthritis (CIA) model, as well as the underlying mechanisms, which have not pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…They are also used as folk remedies for treating RA 10 , 14 – 16 . Pharmacological studies showed that RMF 17 and LJF-containing formulas 18 , 19 can attenuate collagen-induced arthritis (CIA). We previously found that a standardized ethanolic extract of RL (RLE for short) has anti-RA effects in CIA rats 20 .…”
Section: Introductionmentioning
confidence: 99%
“…They are also used as folk remedies for treating RA 10 , 14 – 16 . Pharmacological studies showed that RMF 17 and LJF-containing formulas 18 , 19 can attenuate collagen-induced arthritis (CIA). We previously found that a standardized ethanolic extract of RL (RLE for short) has anti-RA effects in CIA rats 20 .…”
Section: Introductionmentioning
confidence: 99%
“…We found that 4-HMC suppresses the production of inflammatory cytokines and bone destruction in CIA mice. These inflammatory cytokines promote the synthesis of MMPs, which are matrix-degrading enzymes, responsible for joint destruction through cartilage or bone degradation as well as angiogenesis promotion in RA ( Wang et al, 2015 ). In the case of RA patients, MMPs contribute to cartilage destruction ( Otero and Goldring, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that oral administration of an extract of Yingshi attenuated the severity of CIA rats without showing any observable adverse effects 21 . Jinyinhua together with other herbs have been demonstrated to improve conditions in CIA mice 37 . In the present study, we demonstrated that the herbal formula RL significantly improved the clinical conditions throughout the course of disease in CIA rats without observable adverse effects.…”
Section: Discussionmentioning
confidence: 99%